Apakah Stock Split Berpengaruh terhadap Abnormal Return dan Volume Perdagangan Saham? - Iman Wahyudi; Enggar Trijunanto (Sekolah Pascasarjana Perbanas Jakarta, 2022)
Abstract This study aims to examine the difference between abnormal returns and stock trading volume before and after the stock split of public companies on the Indonesian Stock Exchange. The study was conducted by using 55 samples of companies listed on the Indonesian Stock Exchange (IDX) for the period 2013 - 2017 which carried out a stock split. The paired sample t-test is conducted to determine whether there is a significant difference between the abnormal return and the volume of stock trading before and after the stock split. The results of the study show that there are differences in abnormal returns and stock trading volume before and after the stock split. Keywords: Stock Split, Abnormal Stock Return, Stock Trading Volume